Evaluasi Tanggung Jawab Pelaku Usaha Terhadap Perlindungan Konsumen Dilihat dari Perspektif Hukum Pembatalan Penerbangan - Patricia Margaretha, Irene; Sudiro, Amad (UNES Law Review, 2023)
This research aims to evaluate the responsibilities of business actors, especially airlines, regarding consumer protection in the context of flight cancellations, with a focus on the legal perspective. Flight cancellations are often a complex issue, raising questions about the rights and obligations of business actors as well as the protection provided to consumers. This research will analyze the legal framework that regulates consumer rights and the responsibilities of business actors regarding flight cancellations. This legal approach will include a review of applicable aviation regulations, air carriage agreements, and consumer protection laws. In addition, this research will evaluate the extent to which the implementation of business actors' responsibilities is in accordance with applicable legal provisions and the impact on consumer protection.